Bilateral gluteal abscess caused by Kluyvera cryocrescens: a case report - Nautiyal, Sulekha; Jauhari, Shalabh; Pandey, Kxitiza (International Journal of Research in Medical Sciences, 2019)
Kluyvera is a relatively new genus, belonging to family Enterobacteriaceae. This organism colonizes mainly respiratory and gastrointestinal tract. It has also been reported from various environmental sources. Due to a rise in immune-compromised states and ease of identification using automated methods rare organisms are now being reported with their role as potential opportunistic pathogens. Meticulous detailed identification and reporting of pathogens like Klyuvera to differentiate it from other members of Enterobacteriaceae can lead to solving the pathogenic importance of such organisms. We report a case of bilateral gluteal abscess due to Kluyvera cryocrescens in an obese diabetic adult male.